Performance management : measure and improve the effectiveness of your employees - Luecke, Richard; Hall, Brian J.; Harvard Business School (Boston, Mass. : Harvard Business School Press, 2006)
'Performance Management' will help managers use informal performance assessments and feedback as part of their regular interactions with employees. Readers will learn to prepare for a formal performance meeting with a direct report, document a performance meeting, and create a development plan with the employee.
Goals: guides to action -- Motivation: the not-so-secret ingredient of high performance -- Monitoring performance: looking for what's going wrong and right -- Closing gaps and improving performance : the basics of coaching -- Becoming a better coach : beyond the basics -- Formal performance appraisal: improving results through feedback -- Employee development: helping people grow in their careers -- Intractable performance problems: face them head-on -- Epilogue: what leaders must do -- Appendix A: Useful implementation tools -- Appendix B: Handling a dismissal.
Includes bibliographical references (pages 137-138) and index.
Description based on print version record.
Keywords: Personnel management; Performance standards; Führung; Performance standards; Personnel management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books